Availability of Support and Services for Aural Rehabilitation of Children with Hearing Impairment in Punjab – A Survey of Parental Perception - Hina Noor, Manzoor Arif, (PJE, 2023)
Involvement of parents in rehabilitation process is of vital importance. Parental perception and satisfaction from the available support and services are the indicators of their (un)met specific needs. The objectives of the study were to assess the parental perception about the level of available support from different personnel involved in the process of aural rehabilitation and to highlight the parental needs and recommendations for aural rehabilitation of children with hearing impairment (HIC). A survey was conducted from October 2014 to January 2015 to collect demographic data, information about level of support of different personnel as received by the parents, their opinion and recommendation about further required support. The sample comprised of 30 government special education institutes from which 308 questionnaires, filled by the parents of the HIC studying in these institutions hearing impairment in the families of HIC, lack of available support from personnel involved in aural rehabilitation and documented parental demands and recommendations. It was concluded that future planning of provisions for aural rehabilitation may be more effective, if aligned with the requirements and preferences expressed by parents of HIC.